“Urbanistic Architecture” according to Raul Lino. Visions of the Portuguese city in the first half of the 20th century (1900-1948) - Pereira, P. M. (Enquiry The ARCC Journal for Architectural Research, 2020)
Over a period of nearly one hundred years, Raul Lino (1879-1974) experienced the profound political, social and economic changes that marked the twentieth century in Portugal. Having been born during the Constitutional Monarchy (1822-1910), he lived through the First Republic (1910-1926), the Military Dictatorship (1926-1933), the Second Republic, or Estado Novo (New State, 1933-1974), and died shortly after the Carnation Revolution of 25 April 1974, at the dawning of the Third Republic. He was an architect who published prolifically in Portugal, having become known through his advocacy of the Campanha da casa Portuguesa (Portuguese House Campaign), which provoked a great deal of controversy. The debate peaked with the Polémica da casa Portuguesa (Polemic of the Portuguese house) at the Calouste Gulbenkian Foundation in 1970, after the inauguration of the retrospective exhibition on Raul Lino. He is less known for the quality of his transversal synthesis conceived between urbanism, architecture, the decorative arts, and its underlying affirmation of an idea of the city, which we conjecture from our analysis of his narrative. This analysis concentrates on eleven case studies that encompasses architectural projects, urbanistic plans and technical advice limited to the first half of the 20th century. The broad, cross-disciplinary position of Lino was defended in the same year as the First National Architecture Congress (1948), whose proposals ratified in Portugal the orthodoxy principles of modern architecture and urban planning for the new universal man-type, established in 1933 by the International Congresses of Modern Architecture (CIAM). Quoting Aristotle, Raul Lino conceived the city as the locus of happiness, shaping forms of consensus between tradition and modernity by means of an architecture at the scale of man and in proportion to his circumstance, consistently outlining a modern possibility of continuity.